ANALISIS YURIDIS PELAKSANAAN PENGADAAN BARANG DAN JASA PEMERINTAH BERDASARKAN PERATURAN PRESIDEN NO. 16 TAHUN 2018 TENTANG PENGADAAN BARANG DAN JASA PEMERINTAH SEBAGAIMANA TELAH DIUBAH DENGAN PERPRES NO. 12 TAHUN 2021 TENTANG PENGADAAN BARANG DAN JASA PEM - Gintar Hasugian; Sujono (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2025)
This study aims to analyze corruption in the implementation of government procurement of goods and services based on Presidential Regulation No. 16 of 2018 concerning Government Procurement of Goods and Services as amended by Presidential Regulation No. 12 of 2021. The method used is normative juridical with a regulatory and conceptual approach. The study outlines the provisions of Presidential Regulations 16/2018 and 12/2021, as well as the anti-corruption regulations in Law No. 31 of 1999 in conjunction with Law No. 20 of 2001, supported by studies of court decisions and the latest scientific literature. The results of the study indicate that although the second Presidential Regulation emphasizes the principles of transparency, accountability, and the use of an e-procurement system, corrupt practices—such as collusion in auction winners, specification manipulation, and price markups—remain rife. Weak internal oversight, overlapping authority, and lax administrative sanctions are driving factors for irregularities. In response, the study recommends: (1) strengthening the independence and capacity of procurement oversight bodies, (2) simplifying and real-time auditing of the e-procurement system, (3) sharpening administrative and criminal sanctions in the Presidential Decree, and (4) an integrity training program for procurement officials. Implementation of these recommendations is expected to increase the effectiveness of preventing and prosecuting corruption in government procurement of goods and services.